In vitro Properties of Methanol Extract and Sodium Alginate of Sargassum polycystum C. Agardh Brown Seaweed Collected from Malaysia - Jamie Mei-Lin Kok,; Ching-Lee Wong, (Tropical Life Sciences Research, 2022)
The edible brown seaweed, Sargassum polycystum C. Agardh was harvested from the coastal region of Malaysia. In this study, analysis of the nutrition and metal content in the methanol extract showed positive for sodium, potassium, magnesium, vitamins A and E and arsenic contamination. The brine shrimp lethality assay (BSLA) revealed the extract to be non-toxic with LC50 value of 15.60 mg mL?1 (LC50 > 1). The antioxidant and antibacterial activities of the methanol extract were measured through various bioassays. The structural and physicochemical characterisation of the NaAlg, analysed through the 1H-NMR analysis revealed the M:G ratio of NaAlg at 0.733 with mannuronic (M) and guluronic (G) fractions at FM = 0.423 and FG = 0.577, respectively. The degraded NaAlg through methods of ultraviolet irradiation and sonication showed an increment in the in vivo antioxidant activities at intervals of 15 min, 30 min, 60 min, 90 min and 120 min. The Fourier transform infrared spectroscopy (FTIR) spectra of polysaccharides taken before and after UV irradiation showed breakage of covalent bonds and thus, increase in the intensity of both O?H and C?O stretching vibrations. Therefore, the increment in antioxidant activities observed in the treated samples were related to changes seen in their molecular structures. Rumpai laut coklat yang boleh dimakan, Sargassum polycystum C. Agardh dituai dari kawasan pantai Malaysia. Dalam kajian ini, analisis kandungan nutrisi dan logam dalam ekstrak metanol menunjukkan ia positif untuk natrium, kalium, magnesium, vitamin A dan E dan pencemaran arsenik. Brine shrimp lethality assay (BSLA) mendedahkan ekstrak tersebut tidak bertoksik dengan nilai LC50 15.60 mg mL?1 (LC50 > 1). Aktiviti antioksidan dan antibakteria ekstrak metanol diukur melalui pelbagai bioassai. Pencirian struktur dan fizik NaAlg yang dianalisis melalui analisis 1H-NMR, mendedahkan nisbah M:G NaAlg pada 0.733 dengan pecahan manuronik (M) dan guluronik (G) masing-masing pada FM = 0.423 dan FG = 0.577. NaAlg yang dinyahgred melalui kaedah sinaran ultraviolet (UV) dan sonikasi menunjukkan peningkatan dalam aktiviti antioksidan in vivo pada selang masa 15 minit, 30 minit, 60 minit, 90 minit dan 120 minit. Spektra FTIR polisakarida yang diambil sebelum dan selepas sinaran UV menunjukkan kerosakan ikatan kovalen dan dengan itu, peningkatan dalam keamatan kedua-dua getaran regangan O?H dan C?O. Oleh itu, peningkatan dalam aktiviti antioksidan yang diperhatikan dalam sampel yang dirawat berkait dengan perubahan yang dilihat dalam struktur molekul.